THE IMPACT OF PSYCHOSOCIAL CLIMATE IN EDUCATION ON AGGRESSIVE AND PROSOCIAL BEHAVIOR OF THE STUDENTS - Trajchevska, Marija; Boshkovska, Emilija (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
Abstract  Introduction: Psychosocial climate is a general term for set a term of variant types and degrees of relationships in a given social climate. The construct of a psychosocial climate contains number of a different dimensions, according to which two or more formally similar environments are different in experience with their members. Favorable psychosocial climate in schools is a condition for effective study, and at the same time better education quality. From the multitude of components or dimensions of the climate in education, we will list a few of them which greatly influence the student`s results and their achievements, which are: clear rules, competition, teachers support, connection, teachers control, order and organization. As known forms of psychosocial behavior of the students stand out Aggressive and Prosocial behavior. GOAL: To determine if it exists relationship between different dimensions of psychosocial climate in the classroom (clear rules, competition, teacher support, connections, teachersâ€™ control, and order and organization) with the prosocial and aggressive behavior of the students. Materials and methods : The research was made in the Prime School Nikola Karev in Kochani. Respondents are participants of primary education. Inclusion criteria are: students must be on age of 12-13 (eight class), age corresponding to the age for which the questionnaires are intended. Exclusion criteria include children who have not attended classes for an extended period of time. Are included 3 classes with total 72 respondents. Results: Relative to the arithmetic mean dimensions clear rules (M=15.63), teachers support (M=36.49), connection (M=33.61), teachers control (M=28.47), order and organization (M=28.49) are solid approved by the students. On the contrary, competition as a dimension, with arithmetical mean (M=14.76), it is less represented in the class than the other dimensions. As can be seen from the standard deviation, the dimension of teacher support has more fragmentation of the scores (SD=8.36), unlike dimension competition which shows less fragmentation of the scores (SD=3.03). The results showed that the prosocial behavior (M=31.06) is more presented among students, which means that they are prepared for collaboration with their classmates, unlike the aggressive behavior (M=22.97) which is less presented. In relation to standard deviation, the aggressive behavior has more fragmentation of the scores (SD=8.78), unlike the prosocial behavior where can be seen less fragmentation of the scores (SD=8.48). It can be seen that there is a positive connection significant on level.